Fractional carbon dioxide vaginal laser treatment of stress urinary incontinence: Remodeling of vaginal tissues and improving pelvic floor structures. Issue 3 (7th February 2023) - Gao, Lin; Wang, Yuanli; Wen, Wei; Duan, Yunyan; Li, Zhaoyang; Dang, Erle; Li, Peng; Yu, Lei; Zhou, Chenxi; Lu, Meiheng; Wang, Gang
Abstract: Objective: To demonstrate remodeling of vaginal biomechanical and physiological properties using vaginal fractional carbon dioxide (CO2 ) laser treatment of stress urinary incontinence (SUI). Materials and Methods: The study cohort included 26 patients with SUI between October 2019 and November 2020. Patients were treated with two sessions of FemTouch vaginal fractional CO2 laser with a one‐month interval. Three subjective assessments were administered to all patients: female sexual function index (FSFI), vaginal health index score (VHIS), and international consultation on incontinence questionnaire‐short form (ICIQ‐SF). Vaginal tissue biopsies were taken from 6 patients before treatment and one‐month after the final treatment. Vaginal tactile imaging (VTI) measurements, ultrasonography, and magnetic resonance imaging (MRI) scans were performed before treatment and 10–12‐months after treatment in 10, 9, and 6 patients, respectively. Results: The average age of the cohort was 39.5 ± 12.0 years. The overall scores for FSFI, VHIS, and ICIQ‐SF significantly improved in patients after each treatment sessions as compared with baseline scores. VTI showed significantly increased pressure resistance of both the anterior and posterior vaginal walls after treatment. Ultrasonography showed significant decreases in bladder neck mobility and urethrovesical angle during the Valsalva maneuver after treatment. MRI scans showed significant decreases in the length of the vaginal anterior wall after treatment. Histological examination confirmed that the laser treatment led to a thicker stratified squamous epithelium layer as compared to the baseline. Conclusions: Our results demonstrated that vaginal fractional CO₂ laser treatment can restore vaginal biomechanical and physiological properties by increasing vaginal tightening and improving pelvic floor structures.